\(Typhonium rhizomatosum\) (Araceae), a new record for the flora of Vietnam - Nguyen-Phi, Nguyen; Tien Van, Hong; Luu, Hong Truong (Academia Journal of Biology, 2023)
Typhonium rhizomatosum A.Galloway & P.Schmidt is reported here as a new record to the flora of Vietnam. It is described and illustrated with detailed photographs of key morphological characters. Besides, the sequences of matK and trnL-F regions were also successfully sequenced to confirm its identity.